EFFECTIVENESS OF SHORT-TERM PSYCHOTHERAPY OF DEPRESSIVE AND ANXIETY DISORDERS - A. S. Elzesser; R. V. Kadyrov; E. V. Markelova (Вестник Кемеровского государственного университета, 2018)
The article features the effectiveness of different psychotherapeutic approaches to psychological care in order to determine the most  effective type of psychotherapy for depressive and anxiety disorders.  The research considers the place of anxiety and depressive disorders in the ICD-10 classification; the article  notes a contradiction between the theoretical separation of these  disorders in ICD-10 and the frequent comorbidity (50 %) of these  disorders in the clinical picture; the authors justify the choice of one  form of psychotherapy for disorders of the anxiety-depressive  spectrum. The paper contains an overview of the results of meta- analyses for person-centered, psychodynamic, cognitive-behavioral  psychotherapy. It describes and analyses the most common  approaches to psychotherapy of anxiety-depressive spectrum  disorders by applying combined pharmacotherapy and  psychotherapy in the cognitive-behavioral and interpersonal  approaches. Based on the overview of meta-analyses of  evidencebased studies of the effectiveness of these types of  psychotherapy, it is concluded that short-term interpersonal and  cognitive-behavioral approaches are most preferable in the therapy  of anxiety and depressive disorders. There is a tendency towards  further integration of approaches on the methodological basis of cognitive-behavioral therapy.